3LPP pipe joint anti-corrosion mastic glue, heat shrink tape and preparation method thereof
By improving the formula of masti oil glue, adding materials such as maleic anhydride grafted hydrogenated thermoplastic elastomer and ethylene methyl methacrylate, the high temperature installation and high cost of 3LPP pipeline node repair anticorrosion materials are solved, and higher bonding strength and high temperature resistance are achieved, and it is suitable for a variety of pipeline types.
Patent Information
- Application Number
- CN202310588542.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-24
AI Technical Summary
In the prior art, the anticorrosion materials for the node repair of 3LPP pipelines require high temperature installation and are expensive, making it difficult to meet the anticorrosion needs of high-temperature 3LPP pipelines.
A 3LPP pipeline repair and anti-corrosion mastis glue is developed, which contains maleic anhydride grafted hydrogenated thermoplastic elastomer, ethylene methyl methacrylate and cage polysilsesquioxane and other materials, to improve the maximum operating temperature and high temperature resistance of the hot melt adhesive through improved formulation.
It achieves better bonding strength and high temperature resistance at installation temperatures below 140℃, reduces construction costs and engineering costs, and is also suitable for 3LPP/3LPE/FBE pipeline node repair and corrosion protection.
Smart Images

Figure BDA0004244316840000061 
Figure BDA0004244316840000071 
Figure BDA0004244316840000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a mastic adhesive and a heat shrinkable tape for 3LPP pipeline patching and anti-corrosion, and a preparation method thereof. Background Art
[0002] At present, the types of polyolefin outer anti-corrosion layers of buried steel pipelines are mainly divided into two categories, three-layer polyethylene coating (3LPE) and three-layer polypropylene coating (3LPP). Due to the different performance characteristics of each type of anti-corrosion layer, the materials used for the anti-corrosion of pipeline nodes are also very different. At present, the anti-corrosion of 3LPE-coated pipeline nodes is mainly made of radiation cross-linked polyethylene heat shrinkable tape, while the anti-corrosion of 3LPP-coated pipeline nodes is mainly made of radiation cross-linked polypropylene heat shrinkable tape.
[0003] Radiation cross-linked polypropylene heat shrink tape is a strip material formed by coating modified polypropylene hot melt adhesive on radiation cross-linked polypropylene substrate. When used, first apply solvent-free epoxy primer on the surface of the steel pipe, and then shrink the heat shrink tape to the pipe node by heating. The hot melt adhesive is heated to melt, and the solvent-free epoxy coating and PP coating at the weld joint form a good bonding seal, thereby protecting the steel pipe from corrosion. According to the principle of similar compatibility, in order to form a good bond with the PP coating of the pipe body and improve the temperature resistance of the hot melt adhesive, most polypropylene hot melt adhesives use polypropylene modified hot melt adhesives, and their melting points are all above 140°C. In order to fully melt the hot melt adhesive, the installation temperature needs to reach 180-200°C. It is difficult to increase the temperature to above 180°C with a torch, so the installation of polypropylene heat shrink tape usually requires medium frequency heating equipment. If the construction site of the polypropylene heat shrink tape is not equipped with medium frequency equipment, it is usually difficult to ensure the installation quality of the heat shrink tape. However, the price of medium frequency equipment ranges from hundreds of thousands to millions, and it also requires millions of mobile high-power power facilities and lifting equipment, which greatly increases the project cost.
[0004] The maximum operating temperature of the existing radiation cross-linked polyethylene heat shrink tape is 80°C. Since its hot melt adhesive is mainly EVA modified hot melt adhesive and has poor adhesion to PP coating, it is usually only used for 3LPE pipeline node patching and anti-corrosion. The maximum operating temperature of the radiation cross-linked polypropylene heat shrink tape can reach 110°C. Its hot melt adhesive is mainly polypropylene modified hot melt adhesive, which has poor adhesion to PE coating, and the installation temperature is as high as 190°C or above, so it can only be used for 3LPP pipeline node patching and anti-corrosion. The existing high-temperature mastic adhesive uses amorphous materials such as thermoplastic elastomers, asphalt and polyisobutylene. When the temperature reaches 100°C, it has good fluidity and adhesion. During installation, it only needs to be baked with a torch to shrink the substrate into place. The mastic adhesive can form a good bond with the steel pipe, the pipe body anti-corrosion layer and the substrate. The construction operation is simple and the construction cost is low, which can greatly reduce the cost of pipeline construction. However, since mastic hot melt adhesive mostly uses asphalt, its weather resistance and high temperature performance are poor. It will flow when the temperature exceeds 80°C, making it difficult to use it for high-temperature 3LPP pipeline node anti-corrosion.
[0005] Therefore, it is necessary to develop a heat shrink material that can be used for 3LPP / 3LPE / FBE pipeline node patching and anti-corrosion, with an installation temperature of only below 140°C and no need for medium frequency equipment for installation. Summary of the invention
[0006] In view of the above technical problems, the present invention discloses a mastic adhesive for 3LPP pipeline patching and anti-corrosion, a heat shrinkable tape and a preparation method thereof, which will not flow when the temperature exceeds 100°C, thereby increasing the maximum use temperature of the mastic-based hot melt adhesive, increasing the wettability of the mastic hot melt adhesive to the adherend, increasing the bonding strength and high temperature resistance of the adhesive, achieving better performance, and the installation temperature only needs to be below 140°C.
[0007] To this end, the technical solution adopted by the present invention is:
[0008] A mastic glue for 3LPP pipeline patching and anti-corrosion, comprising the following components and their mass percentages: 15-25% maleic anhydride grafted hydrogenated thermoplastic elastomer, 3-7% high melt index ethylene methyl methacrylate, 15-20% low melt index ethylene methyl methacrylate, 3-7% cage polysilsesquioxane, 8-15% medium molecular weight polyisobutylene, 3-5% low molecular weight polyisobutylene, 15-25% tackifying resin, 10-20% nano active filler, 0.5-1% antioxidant, 0.5-1% anti-aging agent, and 1.0-1.5% masterbatch. The maleic anhydride grafted hydrogenated thermoplastic elastomer is maleic anhydride grafted SEBS (hydrogenated SBS), i.e., SEBS-MAH, and the maleic anhydride grafting rate of the maleic anhydride grafted hydrogenated thermoplastic elastomer is 1.0-1.5%.
[0009] The technical scheme of the present invention starts with the formula of mastic hot melt adhesive, selects maleic anhydride grafted hydrogenated thermoplastic elastomer with excellent high temperature resistance and ethylene methyl methacrylate with high melting point as main film-forming resin, and adds appropriate amount of medium molecular weight polyisobutylene, low molecular weight polyisobutylene and high softening point tackifying resin and other materials, wherein the nano active filler has large particle surface area, and the surface is covered with unstable atoms with high surface energy, which is very easy to adsorb and bond with foreign atoms, and can firmly adsorb low molecular weight polyisobutylene and tackifying resin; the cage-type polysilsesquioxane has an inorganic core composed of a silicon oxygen skeleton with Si-O alternately connected, and its shape is like a "cage", which can inhibit the chain movement of polymer molecules. These substances in the formula are mixed and reacted according to appropriate proportions, thereby improving the maximum use temperature and high temperature resistance of mastic hot melt adhesive, improving the wettability of mastic hot melt adhesive to adherends, thereby improving the bonding strength of the adhesive, and having good thermal stability, mechanical properties and flame retardancy. Among them, high melt index ethylene methyl methacrylate has high room temperature bonding strength and good peeling state, but low high temperature bonding strength; low melt index ethylene methyl methacrylate has high high temperature bonding strength, but it is easy to have interface damage at room temperature, resulting in low room temperature bonding strength. This technical solution uses a proper proportion of high melt index ethylene methyl methacrylate and low melt index ethylene methyl methacrylate to balance the high temperature bonding performance and room temperature bonding performance of the adhesive.
[0010] As a further improvement of the present invention, the mastic glue for 3LPP pipeline patching and anti-corrosion contains the following components and their mass percentages: 18-22% maleic anhydride grafted hydrogenated thermoplastic elastomer, 4-6% high melt index ethylene methyl methacrylate, 15-18% low melt index ethylene methyl methacrylate, 4-6% cage polysilsesquioxane, 10-12% medium molecular weight polyisobutylene, 3-5% low molecular weight polyisobutylene, 18-22% tackifying resin, 12-18% nano active filler, 0.5-1% antioxidant, 0.5-1% antioxidant, and 1.0-1.5% masterbatch.
[0011] As a further improvement of the present invention, the maleic anhydride grafted hydrogenated thermoplastic elastomer has a melt flow index of 10-50 g / 10 min at 230°C. Further, the maleic anhydride grafted hydrogenated thermoplastic elastomer can be selected from brands such as FG1901 and MD6684 of Kraton, USA, or SEBS can be purchased to graft maleic anhydride by itself. Further preferably, the styrene content of the hydrogenated thermoplastic elastomer is 10-35%.
[0012] As a further improvement of the present invention, the methyl methacrylate content of the low melt index ethylene methyl methacrylate is 5-15%. Further, the melt flow index of the low melt index ethylene methyl methacrylate is 2-10g / 10min. Further, the optional brands of the low melt index ethylene methyl methacrylate include WD301-F (MMA=10%, MI=7), WD201-F (MMA=10%, MI=2g / 10min), WD203-1 (MMA=5%, MI=2), CM8013 (MMA=12.5%, MI=3.5) and the like of Sumitomo of Japan.
[0013] As a further improvement of the present invention, the methyl methacrylate content of the high melt index ethylene methyl methacrylate is 25-35%. Further preferably, the melt flow index of the high melt index ethylene methyl methacrylate is 400-500 g / 10 min. The optional grades of the high melt index ethylene methyl methacrylate include CM5021 (MMA=28%, MI=450 g / 10 min) and CM5022 (MMA=32%, MI=450 g / 10 min) of Sumitomo of Japan.
[0014] As a further improvement of the present invention, the cage-type polysilsesquioxane is at least one of octavinyl cage-type polysilsesquioxane, tetramethylammonium cage-type polysilsesquioxane, acryloxypropyl cage-type polysilsesquioxane, vinyldimethylsiloxy cage-type polysilsesquioxane, dimethylsiloxy cage-type polysilsesquioxane and the like.
[0015] As a further improvement of the present invention, the medium molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 50,000 to 100,000. Further, the medium molecular weight polyisobutylene can be selected from brands such as BASF's B12 and B15, Shandong Hongrui's HRD850, HRD750, HRD950, Hangzhou Shunda's 8850, 8950, 8750, etc.
[0016] As a further improvement of the present invention, the low molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 1000 to 3000. Further, the low molecular weight polyisobutylene can be selected from brands such as BASF's 6240, Korea's Daelim's 2400, and Japan's PIB2300.
[0017] As a further improvement of the present invention, the tackifying resin is at least one of C5 hydrogenated petroleum resin, terpene T-120 or C5 / C9 copolymerized petroleum resin, and the ring and ball softening point of the resin is 120-140° C. Further, the tackifying resin can be selected from brands such as P-125 and P-140 of Idemitsu of Japan.
[0018] As a further improvement of the present invention, the nano-active filler comprises one or more combinations of nano-active calcium carbonate, nano-active talc, and nano-active barium sulfate, wherein the nano-active filler is a surface-modified nano-filler.
[0019] As a further improvement of the present invention, the antioxidant is at least one of antioxidant 1010, antioxidant 1076 or antioxidant SKY-1035.
[0020] As a further improvement of the present invention, the antioxidant is at least one of antioxidant 264, antioxidant 2264, antioxidant HPC, and antioxidant D.
[0021] As a further improvement of the present invention, the masterbatch carrier of the masterbatch is ethylene methyl methacrylate.
[0022] The present invention discloses a method for preparing the above-mentioned mastic glue for 3LPP pipeline patching and anti-corrosion, comprising the following steps:
[0023] Weigh the raw materials according to the formula, heat the kneader to 170-190°C, add maleic anhydride grafted hydrogenated thermoplastic elastomer, low molecular weight polyisobutylene, tackifying resin, antioxidant and anti-aging agent, and stir for more than 15 minutes; adjust the temperature of the kneader to 140-160°C, then add cage-type polysilsesquioxane, high melt index ethylene methyl methacrylate, low melt index ethylene methyl methacrylate and medium molecular weight polyisobutylene, and stir for more than 15 minutes; finally add the remaining materials and stir for more than 1 hour.
[0024] The invention discloses a 3LPP pipeline patching anti-corrosion mastic heat shrinkable tape, which comprises a radiation cross-linked polypropylene substrate and the above-mentioned 3LPP pipeline patching anti-corrosion mastic adhesive, wherein the 3LPP pipeline patching anti-corrosion mastic adhesive is coated on one surface of the radiation cross-linked polypropylene substrate.
[0025] The invention discloses a method for preparing the above-mentioned 3LPP pipeline patching anti-corrosion mastic heat shrinkable tape, comprising: delivering the 3LPP pipeline patching anti-corrosion mastic adhesive to an extruder discharge port through a gear pump, extruding and coating it on a surface of a radiation cross-linked polypropylene substrate, and pressing to obtain a finished product.
[0026] As a further improvement of the present invention, the barrel and die temperature of the extruder are set as follows:
[0027] Barrel: first zone: 120~140℃, second zone, 130~150℃, third zone, 135~155℃, fourth zone, 140~160℃, fifth zone, 140~160℃, sixth zone, 140~160℃;
[0028] Die head: first zone, 140~160℃, second zone, 140~160℃, third zone, 140~160℃, fourth zone, 140~160℃, fifth zone, 140~160℃.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] First, the high-temperature mastic heat shrink tape made of mastic glue for 3LPP pipeline patching anti-corrosion of the technical solution of the present invention has a maximum operating temperature of 100°C and a lower cost, so that the 3LPP pipeline node patching anti-corrosion material is no longer limited to the 3PP heat shrink tape which is expensive, difficult to construct and has extremely high construction cost, thereby reducing the difficulty and engineering cost of 3PP pipeline construction.
[0031] Second, the technical solution of the present invention increases the maximum operating temperature of mastic-based hot melt adhesive, greatly improves the wettability of mastic hot melt adhesive to adherends, improves the bonding strength and high temperature resistance of the adhesive, has better thermal stability, mechanical properties and flame retardancy, and the installation temperature only needs to be below 140°C. DETAILED DESCRIPTION
[0032] The preferred embodiments of the present invention are described in further detail below.
[0033] A mastic glue for 3LPP pipeline patching and anti-corrosion, comprising the following components and their mass percentages: 15-25% maleic anhydride grafted hydrogenated thermoplastic elastomer, 3-7% high melt index ethylene methyl methacrylate, 15-20% low melt index ethylene methyl methacrylate, 3-7% cage polysilsesquioxane, 8-15% medium molecular weight polyisobutylene, 3-5% low molecular weight polyisobutylene, 15-25% tackifying resin, 10-20% nano active filler, 0.5-1% antioxidant, 0.5-1% anti-aging agent, and 1.0-1.5% masterbatch. The maleic anhydride grafted hydrogenated thermoplastic elastomer is SEBS-MAH.
[0034] Preferably, maleic anhydride grafted hydrogenated thermoplastic elastomer 18-22%, high melt index ethylene methyl methacrylate 4-6%, low melt index ethylene methyl methacrylate 15-18%, cage polysilsesquioxane 4-6%, medium molecular weight polyisobutylene 10-12%, low molecular weight polyisobutylene 3-5%, tackifying resin 18-22%, nano active filler 12-18%, antioxidant 0.5-1%, antioxidant 0.5-1%, masterbatch 1.0-1.5%.
[0035] The maleic anhydride grafted hydrogenated thermoplastic elastomer is maleic anhydride grafted SEBS, the maleic anhydride grafting rate is 1.0-1.5%, the melt flow index at 230°C is 10-50g / 10min, and the optional brands include FG1901 (grafting rate 1.5%) and MD6684 (grafting rate 1.05%) of Kraton, USA. SEBS can also be purchased and grafted with maleic anhydride by oneself. The low melting index ethylene methyl methacrylate has a methyl methacrylate content of 5-15%, a melt flow index of 2-10 g / 10 min, a melting point of 100-110° C., and optional grades include WD301-F (MMA=10%, MI=7), WD201-F (MMA=10%, MI=2 g / 10 min), WD203-1 (MMA=5%, MI=2), CM8013 (MMA=12.5%, MI=3.5 g / 10 min), etc. The high melting index ethylene methyl methacrylate has a methyl methacrylate content of 25-35%, a melt flow index of 400-500 g / 10 min, a melting point of 60-70° C., and optional grades include CM5021 (MMA=28%, MI=450 g / 10 min), CM5022 (MMA=32%, MI=450 g / 10 min), etc., of Sumitomo, Japan. The cage-type polysilsesquioxane (OV-POSS) is at least one of cage-type polysilsesquioxanes such as octavinyl cage-type polysilsesquioxane, tetramethylammonium cage-type polysilsesquioxane, acryloxypropyl cage-type polysilsesquioxane, vinyldimethylsiloxy cage-type polysilsesquioxane, and dimethylsiloxy cage-type polysilsesquioxane.
[0036] The medium molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 50,000 to 100,000, and the optional grades include BASF's B12 and B15, Shandong Hongrui's HRD850, HRD750, HRD950, Hangzhou Shunda's 8850, 8950, 8750, etc. The low molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 1000 to 3000, and the optional grades include BASF's 6240, South Korea's Dalin's 2400, Japan's PIB2300, etc. The tackifying resin is at least one of C5 hydrogenated petroleum resin, terpene T-120 or C5 / C9 copolymerized petroleum resin, and the ring and ball softening point of the resin is 120 to 140°C, and the optional grades include Japan's Idemitsu's P-125, P-140, etc. The nano-active filler includes one or more combinations of nano-active calcium carbonate, nano-active talc, and nano-active barium sulfate. The antioxidant is at least one of antioxidant 1010, antioxidant 1076 or antioxidant SKY-1035. The antioxidant is at least one of antioxidant 264, antioxidant 2264, antioxidant HPC and antioxidant D. The masterbatch carrier of the masterbatch is ethylene methyl methacrylate.
[0037] The preparation method of the above-mentioned mastic glue for 3LPP pipeline patching and anti-corrosion comprises the following steps:
[0038] Weigh the raw materials according to the formula, heat the kneader to 170-190°C, add maleic anhydride grafted hydrogenated thermoplastic elastomer, low molecular weight polyisobutylene, tackifying resin, antioxidant and anti-aging agent, and stir for more than 15 minutes; adjust the temperature of the kneader to 140-160°C, then add cage-type polysilsesquioxane, high melt index ethylene methyl methacrylate, low melt index ethylene methyl methacrylate and medium molecular weight polyisobutylene, and stir for more than 15 minutes; finally add the remaining materials and stir for more than 1 hour.
[0039] The performance indicators and test methods of the obtained 3LPP mastic hot melt adhesive for pipeline patching and anti-corrosion are shown in Table 1.
[0040] Table 1 Performance indicators and test methods of mastic hot melt adhesive for 3LPP pipeline joint anti-corrosion
[0041]
[0042] The embodiment of the present invention also discloses a 3LPP pipe patch anti-corrosion mastic heat shrinkable tape, which includes a radiation cross-linked polypropylene substrate and the 3LPP pipe patch anti-corrosion mastic glue as described above, wherein the 3LPP pipe patch anti-corrosion mastic glue is coated on one surface of the radiation cross-linked polypropylene substrate. The preparation method comprises: conveying the 3LPP pipe patch anti-corrosion mastic glue to the feed port of the extruder through a gear pump, extruding and coating it on one surface of the radiation cross-linked polypropylene substrate, and pressing to obtain a finished product. The barrel and die head temperatures of the extruder are set as follows:
[0043] Barrel: first zone: 120~140℃, second zone, 130~150℃, third zone, 135~155℃, fourth zone, 140~160℃, fifth zone, 140~160℃, sixth zone, 140~160℃;
[0044] Die head: first zone, 140~160℃, second zone, 140~160℃, third zone, 140~160℃, fourth zone, 140~160℃, fifth zone, 140~160℃.
[0045] The radiation-crosslinked polypropylene substrate used in this specific embodiment has a tensile strength of ≥28Mpa at room temperature (see GB / T1040.2 for the test method), an elongation at break ≥400% (see GB / T1040.2 for the test method), a brittle temperature ≤-20°C (see GB / T5470 for the test method), a hardness ≥60Shore D (see GB / T2411 for the test method), resistance to corrosion by acid, alkali, and salt chemical media (7d) ≥85% (see GB / T1040.2 for the test method), and heat aging resistance at 130°C and 100d ≥75% (see GB / T1040.2 for the test method).
[0046] The performance indicators and test methods of the mastic heat shrinkable tape for 3LPP pipeline patching anti-corrosion obtained by the above preparation method are shown in Table 2.
[0047] Table 2 Performance indicators and test methods of mastic heat shrink tape for 3LPP pipeline joint anti-corrosion
[0048]
[0049] The preferred embodiments and comparative examples are described below.
[0050] Example 1
[0051] The invention discloses mastic glue for 3LPP pipeline patching and anti-corrosion, and its components and their mass percentages are: 15% of maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH (MD6684, maleic anhydride grafting rate 1.05%), 3% of high melt index ethylene methyl methacrylate (CM5022), 20% of low melt index ethylene methyl methacrylate (WD301-F), 7% of cage polysilsesquioxane, 15% of medium molecular weight polyisobutylene, 3% of low molecular weight polyisobutylene, 15% of tackifying resin, 19% of nano active filler, 1% of antioxidant, 1% of anti-aging agent and 1% of black masterbatch.
[0052] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 10% and a melt index of 7 g / 10 min, and the high melt index ethylene methyl methacrylate has a methyl methacrylate content of 32% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is octavinyl cage-type polysilsesquioxane.
[0053] The medium molecular weight polyisobutylene is BASF's B12. The low molecular weight polyisobutylene is BASF's 6240. The tackifying resin is C5 hydrogenated petroleum resin P-125. The nano-active filler is nano-active calcium carbonate. The antioxidant is antioxidant 1010. The anti-aging agent is anti-aging agent 264. The masterbatch carrier of the black masterbatch is ethylene methyl methacrylate.
[0054] The preparation method comprises the following steps:
[0055] 1. Weigh the raw materials according to the formula, heat the kneader to 180±10℃, add maleic anhydride grafted hydrogenated thermoplastic elastomer, low molecular weight polyisobutylene, tackifying resin, antioxidant and anti-aging agent, and stir for 30 minutes; 2. Adjust the temperature of the kneader to 150±10℃, add cage-type polysilsesquioxane, ethylene methyl methacrylate and medium molecular weight polyisobutylene, and stir for 25 minutes; 3. Add the remaining materials such as nano-active filler and black masterbatch, and stir for 1.5-2 hours.
[0056] The base material of high temperature mastic heat shrinkable tape is made of radiation cross-linked polypropylene base material, with a base material thickness of 1.0mm and a glue layer thickness of 1.5mm.
[0057] The mixed cement is transported to the discharge port of the extruder through a gear pump, and extruded, coated and pressed into finished products according to the following process:
[0058] Barrel: first zone: 130±10℃, second zone: 140±10℃, third zone: 145±10℃, fourth zone: 150±10℃, fifth zone: 150±10℃; sixth zone: 150±10℃;
[0059] Die head: first zone: 150±10℃, second zone: 150±10℃, third zone: 150±10℃, fourth zone: 150±10℃, fifth zone: 150±10℃.
[0060] Example 2
[0061] On the basis of Example 1, the difference of this embodiment is that the formula of mastic gum is different. Specifically, in this embodiment, the formula is: maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 22% (MD6684, maleic anhydride grafting rate 1.05%), high melt index ethylene methyl methacrylate (CM5022) 6%, low melt index ethylene methyl methacrylate (CM8013) 18%, cage polysilsesquioxane 4%, medium molecular weight polyisobutylene 8%, low molecular weight polyisobutylene 4%, tackifying resin 19%, nano active filler 16%, antioxidant 0.9%, antioxidant 0.9%, black masterbatch 1.2%.
[0062] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 12.5% and a melt index of 3.5 g / 10 min; the high melt index ethylene methyl methacrylate has a methyl methacrylate content of 32% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is tetramethylammonium cage-type polysilsesquioxane.
[0063] The medium molecular weight polyisobutylene is HRD850 from Shandong Hongrui. The low molecular weight polyisobutylene is 2400 from Daelim of South Korea. The tackifying resin is terpene T-120. The nano-active filler is nano-active talc. The antioxidant is antioxidant 1076. The anti-aging agent is anti-aging agent 2264. The masterbatch carrier of the black masterbatch is ethylene methyl methacrylate.
[0064] Example 3
[0065] On the basis of Example 1, the difference of this embodiment is that the formula of mastic gum is different. Specifically, in this embodiment, the formula is: maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 25% (MD6684, maleic anhydride grafting rate 1.05%), high melt index ethylene methyl methacrylate (CM5021) 7%, low melt index ethylene methyl methacrylate (CM8013) 15%, cage polysilsesquioxane 3%, medium molecular weight polyisobutylene 8%, low molecular weight polyisobutylene 4%, tackifying resin 20%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.8%, black masterbatch 1.4%.
[0066] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 12.5% and a melt index of 3.5 g / 10 min; the high melt index ethylene methyl methacrylate has a methyl methacrylate content of 28% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is acryloxypropyl cage-type polysilsesquioxane.
[0067] The medium molecular weight polyisobutylene is 8850 from Hangzhou Shunda. The low molecular weight polyisobutylene is PIB2300 from Japan. The tackifying resin is C5 / C9 copolymer petroleum resin. The nano active filler is nano active barium sulfate. The antioxidant is antioxidant SKY-1035. The antioxidant is antioxidant D. The black masterbatch carrier is ethylene methyl methacrylate.
[0068] Example 4
[0069] On the basis of Example 1, the difference of this embodiment is that the formula of mastic gum is different. Specifically, in this embodiment, the formula is: maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 25% (FG1901, maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate (CM5021) 7%, low melt index ethylene methyl methacrylate (WD301-F) 10%, cage polysilsesquioxane 3%, medium molecular weight polyisobutylene 10%, low molecular weight polyisobutylene 5%, tackifying resin 25%, nano active filler 12%, antioxidant 0.7%, antioxidant 0.8%, black masterbatch 1.5%.
[0070] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 10% and a melt index of 7 g / 10 min; the high melt index ethylene methyl methacrylate has a methyl methacrylate content of 28% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is vinyl dimethylsiloxy cage-type polysilsesquioxane.
[0071] The medium molecular weight polyisobutylene is 8750 from Hangzhou Shunda. The low molecular weight polyisobutylene is PIB2300 from Japan. The tackifying resin is C5 / C9 copolymer petroleum resin. The nano active filler is nano active barium sulfate. The antioxidant is antioxidant HPC. The antioxidant is antioxidant 264. The masterbatch carrier of the black masterbatch is ethylene methyl methacrylate.
[0072] Example 5
[0073] On the basis of Example 1, the difference of this embodiment is that the formula of mastic gum is different. Specifically, in this embodiment, the formula is: maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 20% (FG1901, maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate (CM5022) 5%, low melt index ethylene methyl methacrylate (WD203-1) 15%, cage polysilsesquioxane 5%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0074] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 5% and a melt index of 2 g / 10 min. The high melt index ethylene methyl methacrylate has a methyl methacrylate content of 32% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is a dimethylsiloxy cage-type polysilsesquioxane.
[0075] The medium molecular weight polyisobutylene is HRD750 from Shandong Hongrui. The low molecular weight polyisobutylene is 6240 from BASF. The tackifying resin is C5 hydrogenated petroleum resin P-140. The nano-active filler is nano-active calcium carbonate. The antioxidant is antioxidant 1010. The anti-aging agent is anti-aging agent 264. The masterbatch carrier of the black masterbatch is ethylene methyl methacrylate.
[0076] Example 6
[0077] On the basis of Example 1, the difference of this embodiment is that the formula of mastic gum is different. Specifically, in this embodiment, the formula is: maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 15% (FG1901, maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate (CM5021) 7%, low melt index ethylene methyl methacrylate (WD201-F) 18%, cage polysilsesquioxane 6%, medium molecular weight polyisobutylene 13%, low molecular weight polyisobutylene 4%, tackifying resin 18%, nano active filler 16%, antioxidant 0.8%, antioxidant 0.8%, black masterbatch 1.4%.
[0078] The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 10% and a melt index of 2 g / 10 min. The high melt index ethylene methyl methacrylate has a methyl methacrylate content of 28% and a melt index of 450 g / 10 min. The cage-type polysilsesquioxane is a dimethylsiloxy cage-type polysilsesquioxane.
[0079] The medium molecular weight polyisobutylene is HRD950 from Shandong Hongrui. The low molecular weight polyisobutylene is 2400 from Daelim of South Korea. The tackifying resin is C5 hydrogenated petroleum resin. The nano active filler is nano active calcium carbonate. The antioxidant is antioxidant 1010. The anti-aging agent is anti-aging agent 264. The masterbatch carrier of the black masterbatch is ethylene methyl methacrylate.
[0080] Comparative Example 1
[0081] Based on Example 5, the difference of this comparative example is that the maleic anhydride grafting rate of the maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH in the mastic gum formula is 0.5%. The rest is the same as Example 5.
[0082] Specifically, the formula of this comparative example is:
[0083] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 20% (maleic anhydride grafting rate 0.5%), high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, cage polysilsesquioxane 5%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0084] Comparative Example 2
[0085] Based on Example 5, the difference of this comparative example is that the maleic anhydride grafting rate of the maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH in the mastic gum formula is 1.7%, and the others are the same as Example 5.
[0086] Specifically, the formula of this comparative example is:
[0087] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 20% (maleic anhydride grafting rate 1.7%), high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, cage polysilsesquioxane 5%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0088] Comparative Example 3
[0089] Based on Example 1, the main difference of this comparative example is that the amount of maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH in the mastic gum formula is 10%, and the rest is the same as Example 1.
[0090] Specifically, the formula of this comparative example is:
[0091] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 10% (maleic anhydride grafting rate 1.05%), high melt index ethylene methyl methacrylate 3%, low melt index ethylene methyl methacrylate 20%, cage polysilsesquioxane 6%, medium molecular weight polyisobutylene 15%, low molecular weight polyisobutylene 3%, tackifying resin 20%, nano active filler 20%, antioxidant 1%, antioxidant 1%, black masterbatch 1%.
[0092] Comparative Example 4
[0093] On the basis of Example 2, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0094] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 30% (maleic anhydride grafting rate 1.05%), high melt index ethylene methyl methacrylate 7%, low melt index ethylene methyl methacrylate 10%, cage polysilsesquioxane 3%, medium molecular weight polyisobutylene 10%, low molecular weight polyisobutylene 5%, tackifying resin 25%, nano active filler 7%, antioxidant 0.7%, antioxidant 0.8%, black masterbatch 1.5%.
[0095] The rest is the same as Example 2.
[0096] Comparative Example 5
[0097] On the basis of Example 4, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0098] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 10% (maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate 3%, low melt index ethylene methyl methacrylate 20%, cage polysilsesquioxane 6%, medium molecular weight polyisobutylene 15%, low molecular weight polyisobutylene 3%, tackifying resin 20%, nano active filler 20%, antioxidant 1%, antioxidant 1%, black masterbatch 1%.
[0099] The rest is the same as Example 4.
[0100] Comparative Example 6
[0101] On the basis of Example 4, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0102] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 30% (maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate 7%, low melt index ethylene methyl methacrylate 10%, cage polysilsesquioxane 3%, medium molecular weight polyisobutylene 10%, low molecular weight polyisobutylene 5%, tackifying resin 25%, nano active filler 7%, antioxidant 0.7%, antioxidant 0.8%, black masterbatch 1.5%.
[0103] The rest is the same as Example 4.
[0104] Comparative Example 7
[0105] On the basis of Example 5, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0106] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 20% (maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, cage polysilsesquioxane 5%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, common active filler calcium carbonate 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0107] The rest is the same as Example 5.
[0108] Comparative Example 8
[0109] On the basis of Example 5, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0110] Maleic anhydride grafted hydrogenated thermoplastic elastomer SEBS-MAH 20% (maleic anhydride grafting rate 1.5%), high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 20%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0111] The rest is the same as Example 5.
[0112] Comparative Example 9
[0113] On the basis of Example 5, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0114] Thermoplastic elastomer SBS (styrene-butadiene-styrene block copolymer) 20%, high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0115] The rest is the same as Example 5.
[0116] Comparative Example 10
[0117] On the basis of Example 5, the difference of this comparative example is that the formula of mastic gum is different. Specifically, the formula of this comparative example is:
[0118] Thermoplastic elastomer SEBS (styrene-ethylene-butylene-styrene block copolymer) 20%, high melt index ethylene methyl methacrylate 5%, low melt index ethylene methyl methacrylate 15%, medium molecular weight polyisobutylene 12%, low molecular weight polyisobutylene 4%, tackifying resin 21%, nano active filler 15%, antioxidant 0.8%, antioxidant 0.7%, black masterbatch 1.5%.
[0119] The rest is the same as Example 5.
[0120] The above embodiments and comparative examples were tested for performance according to Table 1 and Table 2, and the results obtained are shown in Table 3 and Table 4.
[0121] Table 3 Performance results of the embodiments
[0122]
[0123] Table 4 Performance results of comparative examples
[0124]
[0125] The performance test requirements in Table 4 are the same as those in Table 3.
[0126] It can be seen from the performance test results in Table 3 and Table 4 that the embodiment of the technical solution of the present invention can be used for 3LPP pipeline node patching and anti-corrosion with an operating temperature of up to 100°C, and the hot melt adhesive will not drip when the temperature exceeds 120°C, and has high high-temperature shear strength. It can be seen from the various performance test results in Table 3 and Table 4 that the adhesive has high bonding strength and good high-temperature resistance, and has better thermal stability and mechanical properties.
[0127] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A mastic adhesive for 3LPP pipeline patching and anti-corrosion, characterized by: The components and their mass percentages are as follows: 15-25% maleic anhydride grafted hydrogenated thermoplastic elastomer, 3-7% high melt index ethylene methyl methacrylate, 15-20% low melt index ethylene methyl methacrylate, 3-7% cage polysilsesquioxane, 8-15% medium molecular weight polyisobutylene, 3-5% low molecular weight polyisobutylene, 15-25% tackifying resin, 10-20% nano active filler, 0.5-1% antioxidant, 0.5-1% anti-aging agent, and 1.0-1.5% masterbatch; wherein the maleic anhydride grafted hydrogenated thermoplastic elastomer is maleic anhydride grafted SEBS, and the maleic anhydride grafting rate of the maleic anhydride grafted hydrogenated thermoplastic elastomer is 1.0-1.5%; The low melt index ethylene methyl methacrylate has a methyl methacrylate content of 5-15% and a melt flow index of 2-10 g / 10min; the high melt index ethylene methyl methacrylate has a methyl methacrylate content of 25-35% and a melt flow index of 400-500 g / 10min.
2. The 3LPP pipeline joint anti-corrosion mastic adhesive according to claim 1, characterized in that: The components and their mass percentages are as follows: maleic anhydride grafted hydrogenated thermoplastic elastomer 18-22%, high melt index ethylene methyl methacrylate 4-6%, low melt index ethylene methyl methacrylate 15-18%, cage polysilsesquioxane 4-6%, medium molecular weight polyisobutylene 10-12%, low molecular weight polyisobutylene 3-5%, tackifying resin 18-22%, nano active filler 12-18%, antioxidant 0.5-1%, antioxidant 0.5-1%, and masterbatch 1.0-1.5%.
3. The 3LPP pipeline joint anti-corrosion mastic adhesive according to claim 1, characterized in that: The maleic anhydride grafted hydrogenated thermoplastic elastomer has a melt flow index of 10-50 g / 10 min at 230°C.
4. The 3LPP pipeline joint anti-corrosion mastic adhesive according to claim 1, characterized in that: The cage-type polysilsesquioxane is at least one of octavinyl cage-type polysilsesquioxane, tetramethylammonium cage-type polysilsesquioxane, acryloxypropyl cage-type polysilsesquioxane, vinyldimethylsiloxy cage-type polysilsesquioxane, and dimethylsiloxy cage-type polysilsesquioxane.
5. The 3LPP pipeline joint anti-corrosion mastic adhesive according to claim 4 is characterized by: The medium molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 50,000 to 100,000; the low molecular weight polyisobutylene is a polyisobutylene with a molecular weight of 1,000 to 3,000; the tackifying resin is at least one of C5 hydrogenated petroleum resin, terpene T-120 or C5 / C9 copolymerized petroleum resin, and the ring and ball softening point of the resin is 120 to 140° C.; the nano-active filler includes one or more combinations of nano-active calcium carbonate, nano-active talc, and nano-active barium sulfate; The antioxidant is at least one of antioxidant 1010, antioxidant 1076 or antioxidant SKY-1035; The antioxidant is at least one of antioxidant 264, antioxidant 2264, antioxidant HPC, and antioxidant D; The masterbatch carrier of the masterbatch is ethylene methyl methacrylate.
6. The method for preparing the 3LPP pipeline joint anticorrosion mastic glue according to any one of claims 1 to 5, characterized in that: It includes the following steps: Weigh the raw materials according to the formula, heat the kneader to 170-190°C, add maleic anhydride grafted hydrogenated thermoplastic elastomer, low molecular weight polyisobutylene, tackifying resin, antioxidant and anti-aging agent, and stir for more than 15 minutes; adjust the temperature of the kneader to 140-160°C, then add cage-type polysilsesquioxane, high melt index ethylene methyl methacrylate, low melt index ethylene methyl methacrylate and medium molecular weight polyisobutylene, and stir for more than 15 minutes; finally add the remaining materials and stir for more than 1 hour.
7. A mastic heat shrinkable tape for 3LPP pipeline patching and anti-corrosion, characterized by: It comprises a radiation cross-linked polypropylene substrate and the 3LPP pipeline patching anti-corrosion mastic glue as claimed in any one of claims 1 to 5, wherein the 3LPP pipeline patching anti-corrosion mastic glue is coated on one surface of the radiation cross-linked polypropylene substrate.
8. The method for preparing the mastic heat shrinkable tape for 3LPP pipeline patching anti-corrosion according to claim 7, characterized in that: The 3LPP mastic glue for pipeline patching and anti-corrosion is transported to the discharge port of the extruder through a gear pump, extruded and coated on one surface of the radiation-crosslinked polypropylene substrate, and pressed to obtain a finished product; The barrel and die temperature of the extruder were set as follows: Barrel: first zone: 120~140℃, second zone, 130~150℃, third zone, 135~155℃, fourth zone, 140~160℃, fifth zone, 140~160℃, sixth zone, 140~160℃; Die head: first zone, 140~160℃, second zone, 140~160℃, third zone, 140~160℃, fourth zone, 140~160℃, fifth zone, 140~160℃.
Citation Information
Patent Citations
Hot-melt adhesive for preventing corrosion of repaired mouth of gas pipeline and preparation method thereof
CN101824293A
High-temperature mastic cement for corrosion protection and preparation method thereof
CN102408854A